GmNFYA13 Improves Salt and Drought Tolerance in Transgenic Soybean Plants - Ma, Xiao-Jun; Fu, Jin-Dong; Tang, Yi-Miao; Yu, Tai-Fei; Yin, Zhen-Gong; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Xu, Zhao-Shi; Ma, You-Zhi (Frontiers in Plant Science, 2020)
NF-YA transcription factors function in modulating tolerance to abiotic stresses that are serious threats to crop yields. In this study, GmNFYA13, a NF-YA gene in soybean, was strongly induced by salt, drought, ABA and H2O2, and suppressed by tungstate, an ABA synthesis inhibitor. The GmNFYA13 transcripts were detected in different tissues in seedling and flowering stages with the highest levels in roots. GmNFYA13 is a nuclear localization protein with self-activating activity. Overexpression of GmNFYA13 in transgenic Arabidopsis and soybean plants resulted in ABA hypersensitivity and enhanced salt and drought tolerance with higher transcript levels of stress-related genes in comparison to plants without extra copies of GmNFYA13, while suppressing it produced the opposite results. In addition, GmNFYA13 could bind to the promoters of GmSALT3, GmMYB84, GmNCED3 and GmRbohB to regulate their expression abundance in vivo. Results of this study suggested that GmNFYA13 could positively regulate salt and drought tolerance in Arabidopsis and soybean.